Concrete for artificial sand-based PHC pipe pile as well as preparation method and application of concrete

By modifying artificial sand with water glass, carboxylic styrene butadiene latex and polyvinyl alcohol, filling and blocking microcracks, the problem of the reduction in strength of artificial sand-based PHC pipe piles after freeze-thaw cycle is solved, and good resistance is achieved Freezing performance expands its application range.

CN119176702APending Publication Date: 2024-12-24山东华威建工科技有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411366659.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The strength of existing artificial sand-based PHC pipe pile concrete is significantly reduced after freeze-thaw cycle and cannot be suitable for cold areas.

Method used

By soaking artificial sand in a modified solution mixed with water glass, carboxylic styrene butadiene latex and polyvinyl alcohol, microcracks are filled and blocked, reducing aggregation and moisture storage, and improving freezing resistance.

Benefits of technology

It significantly improves the freezing resistance of pipe piles, allowing them to maintain strength during the freeze-thaw cycle, and is suitable for cold areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005066408110000041
    Figure BDA0005066408110000041
  • Figure BDA0005066408110000061
    Figure BDA0005066408110000061
  • Figure BDA0005066408110000071
    Figure BDA0005066408110000071
Patent Text Reader

Abstract

The invention discloses concrete for an artificial sand based PHC pipe pile and a preparation method and application thereof.The concrete is prepared from, by weight, 100 parts of cement, 20-30 parts of admixture, 25-35 parts of modified artificial sand, 40-55 parts of coarse aggregate, 0.1-1 part of water reducing agent and 25-40 parts of water, and the modified artificial sand is obtained by soaking the artificial sand in modification liquid and drying the artificial sand; the modified liquid comprises 5-10 wt% of water glass, 5-7 wt% of carboxylic butadiene-styrene latex and 0.5-1 wt% of polyvinyl alcohol, and the mass volume ratio of the artificial sand to the modified liquid is 1: (2.5-4) g / mL. The artificial sand in the raw materials of the tubular pile concrete is firstly treated by the modified liquid formed by mixing the water glass, the carboxylic butadiene-styrene latex, the polyvinyl alcohol and the water, micro cracks on defective particles of the artificial sand can be filled and blocked, aggregation of centrifugal forming of the tubular pile can be reduced, water is prevented from being stored in the micro cracks, and the service life of the tubular pile is prolonged. And the finally prepared pipe pile has good anti-freezing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete, and in particular relates to concrete for artificial sand-based PHC pipe piles, and a preparation method and application thereof. Background Art

[0002] Prestressed high-strength concrete piles (PHC piles for short) are high-strength concrete products that have been rapidly developed in my country in recent years. Compared with other building foundations, PHC piles not only have the advantages of fast construction speed, low cost, and wide adaptability to geological conditions, but also have excellent seismic performance and high bearing capacity. They have been widely used in pile foundations of seaports, rivers, and bridge projects, and have great market prospects. The production of PHC piles requires low-fluidity concrete, and the strength of the concrete after consolidation reaches C80 grade or above. In order to ensure its excellent and stable performance, high-quality natural river sand is currently basically used as the fine aggregate of PHC pile concrete. However, with the development of national engineering construction, the market demand for sand has gradually increased. Since natural sand is a local resource and cannot be regenerated in a short period of time, there has been a phenomenon of tight supply of natural sand or no sand available.

[0003] Artificial sand is a building material with sand grains made by mechanical processing and crushing natural rocks, ores or industrial waste. Compared with natural sand, artificial sand has the advantages of rich materials, hard texture, little impact of processing seasons, good bonding performance, and various physical indicators are similar to those of natural sand. It is a more suitable material to replace natural sand.

[0004] At present, some researchers have used artificial sand to replace natural sand in the preparation of concrete for PHC pipe piles, such as patent CN112500109B, which discloses a non-autoclaved PHC pipe pile concrete and a non-autoclaved PHC pipe pile production process. One of the non-autoclaved PHC pipe pile concrete can completely replace natural sand with artificial sand by adjusting the gradation of artificial sand and aggregate, and can produce concrete that meets actual production needs. Patent CN105541223B discloses a PHC pipe pile concrete and a preparation method thereof. The PHC pipe pile concrete is composed of the following components: a cementitious material, a synergist, fine aggregate, coarse aggregate, a water reducer and water. The bulk density of the concrete is 2400 to 2600 Kg / m 3 The amount of cementitious material used per cubic meter of concrete is 12-22%, the amount of synergist is 1.0-5%, the amount of fine aggregate is 22-32%, the amount of coarse aggregate is 40-52%, the amount of water reducer is 0.2%-1.0%, and the amount of water is 4.0-7.5%.

[0005] The above is a study on the use of artificial sand instead of natural sand in the preparation of concrete for PHC pipe piles. The prepared PHC pipe pile concrete has excellent strength and ion permeability. Since artificial sand is a mechanically processed product, there are many defective particles with microcracks in the artificial sand due to crushing and grinding. In the centrifugal forming process of the pipe pile, the defective particles are prone to a certain degree of aggregation. Although this aggregation has little effect on properties such as strength and ion permeability, after experiencing multiple freeze-thaw cycles, the water content in the defective particle aggregation area is higher than that in other areas. After freezing, the volume expansion difference between this area and other areas is large, and the concrete produces microcracks. The repeated freeze-thaw cracks continue to expand, and finally the strength is significantly reduced, so that this PHC pipe pile can be used in the south, but cannot be used in the cold north. Therefore, it is necessary to develop an artificial sand-based PHC pipe pile concrete with excellent antifreeze properties to further expand its application. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides an artificial sand-based concrete for PHC pipe piles and a preparation method and application thereof. The artificial sand in the concrete raw material is first treated with a modified liquid mixed with water glass, carboxylated styrene butadiene latex, polyvinyl alcohol and water, which can fill and seal the microcracks on the defective particles of the artificial sand. On the one hand, it can reduce the aggregation of the centrifugal forming of the pipe piles, and on the other hand, it can prevent water from being stored in the microcracks, so that the pipe piles finally have good antifreeze performance.

[0007] To achieve the above object, the present invention adopts the following technical solutions:

[0008] An artificial sand-based concrete for PHC pipe piles comprises the following raw materials in parts by weight: 100 parts of cement, 20-30 parts of admixture, 25-35 parts of modified artificial sand, 40-55 parts of coarse aggregate, 0.1-1 part of water reducer, and 25-40 parts of water. The modified artificial sand is obtained by soaking artificial sand in a modifying liquid and drying the modified liquid. The modifying liquid comprises 5-10wt% of water glass, 5-7wt% of carboxylated styrene butadiene latex, and 0.5-1wt% of polyvinyl alcohol. The mass volume ratio of the artificial sand to the modifying liquid is 1:2.5-4g / mL.

[0009] The carboxylated styrene butadiene latex has a solid content of 45-55wt%, a pH of 5.5-7.0, a Tg of 2-10°C, and an average particle size of 100-200nm.

[0010] In the field of construction, water glass is often used as a plugging agent, but its toughness and water resistance are poor after dehydration and hardening. Carboxylated styrene butadiene latex is a copolymer latex of styrene, butadiene and a small amount of unsaturated carboxylic acid derivatives. It is often used in the full range of latex required by the paper and paperboard coating industry. It is suitable for surface and bottom coating and bonding of decorative base paper, wear-resistant paper, medium and high-grade coated paper, white paper, cardboard, boxboard, etc. In the field of construction, polyvinyl alcohol powder is often used to improve the performance of putty and mortar.

[0011] The inventors used water glass, carboxylated styrene butadiene latex and polyvinyl alcohol in combination to modify artificial sand and found that the frost resistance of pipe pile concrete can be significantly improved. It is speculated that: water glass can improve the interaction between carboxylated styrene butadiene latex and artificial sand to improve the sealing performance, carboxylated styrene butadiene latex can improve the toughness and water resistance of water glass to better cope with freeze-thaw cycles, and polyvinyl alcohol has the function of a surfactant. Under the action of a small amount of polyvinyl alcohol, the rheological properties, bonding properties and surface tension of the modified liquid are improved, which is conducive to the adsorption of water glass and carboxylated styrene butadiene latex by the micro-cracks on the artificial sand, thereby filling and sealing the micro-cracks.

[0012] The modulus of the water glass is 2.0-3.5, and the Baume degree is 30-40.

[0013] The weight average molecular weight of the polyvinyl alcohol is 30,000-50,000.

[0014] The artificial sand has a fineness modulus of 2.2-3.0 and a mud content of ≤1.0%.

[0015] Furthermore, the gradation of the artificial sand is 60-70wt% of the artificial sand with a fineness modulus of 2.2-2.5, and 30-40wt% of the artificial sand with a fineness modulus of 2.5-3.

[0016] The cement is silicate cement with a strength grade of 42.5-52.5.

[0017] The admixture is selected from one or a combination of two or more of fly ash, mineral powder, and silica sand powder.

[0018] Furthermore, the admixture is fly ash.

[0019] Furthermore, the fly ash has a fineness of 20-25%, a water requirement ratio of 80-100%, and a 7-day activity index of not less than 85%.

[0020] The coarse aggregate is a continuously graded natural crushed stone with an average particle size of 5-25 mm.

[0021] The water reducer is selected from one or a combination of polycarboxylic acid high-efficiency water reducer and naphthalene-based high-efficiency water reducer.

[0022] The present invention also provides a method for preparing the above-mentioned artificial sand-based PHC pipe pile concrete, comprising the following steps:

[0023] 1) mixing water glass, carboxylated styrene butadiene latex, polyvinyl alcohol and water to obtain a modified liquid, then soaking the artificial sand in the modified liquid, subjecting it to ultrasonic treatment, draining the water, and drying the modified artificial sand for standby use;

[0024] 2) Add cement, admixture, modified artificial sand, coarse aggregate, water reducing agent and water into a mixer and mix them evenly to obtain concrete for artificial sand-based PHC pipe piles.

[0025] Step 1) The power of the ultrasonic treatment is 300-500W, the frequency is 20-40kHz, the time is 10-20min, and the drying temperature is 60-100°C.

[0026] The present invention also provides use of the artificial sand-based PHC pipe pile concrete in preparing PHC pipe piles.

[0027] Furthermore, the use comprises the following steps:

[0028] The artificial sand-based PHC pipe pile concrete is injected into the pipe pile mold, the mold is closed, and the pipe pile mold after the mold is closed is subjected to prestressing tensioning treatment, centrifugal treatment, steam curing, demoulding, and high-pressure steam curing to obtain the artificial sand-based PHC pipe pile.

[0029] The steps of the centrifugation treatment are sequentially: a low-speed stage of centrifuging at a rotation speed of 50-100 r / min for 1-3 min, a low-medium-speed stage of centrifuging at a rotation speed of 100-150 r / min for 1-3 min, a medium-speed stage of centrifuging at a rotation speed of 200-400 r / min for 3-5 min, and finally a high-speed stage of centrifuging at a rotation speed of 400-600 r / min for 5-10 min.

[0030] The steam curing procedure includes four stages: static, heating, constant temperature and cooling. The static time is 0.5-3.5h, the heating rate in the heating stage is 20-30℃ / h, the temperature in the constant temperature stage is 80-100℃ and the time is 4-8h, and the cooling is natural cooling.

[0031] The high-pressure steam curing includes a temperature increase and pressure increase stage, a constant temperature and pressure stage, and a temperature decrease and pressure reduction stage. The temperature increase and pressure increase stage is to increase the pressure to 0.8-1MPa and the temperature to 160-180°C in 0.5-2.5h; the constant temperature and pressure stage is 4-6h; the temperature decrease and pressure reduction stage is a natural temperature decrease with a pressure reduction rate of 0.3-0.5MPa / h.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] The artificial sand in the raw material of the pipe pile concrete of the present invention is first treated with a modified liquid mixed with water glass, carboxylated styrene butadiene latex, polyvinyl alcohol and water, so that micro cracks on defective particles of the artificial sand can be filled and blocked, which can not only reduce the aggregation of the pipe pile during centrifugal molding, but also prevent water from being stored in the micro cracks, so that the finally prepared pipe pile has good antifreeze performance. DETAILED DESCRIPTION

[0034] The present invention will be further described below in conjunction with specific embodiments, but is not limited to the contents of the specification. Unless otherwise specified, the "parts" described in the embodiments of the present invention are all parts by weight. The reagents used are all commercially available reagents in the art.

[0035] Artificial sand was purchased from Weihui Wanyou Stone Co., Ltd., with a fineness modulus of 2.3 for 60 wt % and a fineness modulus of 3 for 40 wt %.

[0036] Coarse aggregate was purchased from Zhuzhou Aggregate New Materials Co., Ltd. Screening results of 5-10 mm and 10-20 mm crushed stone:

[0037]

[0038] Water glass was purchased from Guangdong Zhengneng Water Glass Co., Ltd., the modulus was purchased from 3.1, and the Baume degree was 37.

[0039] Carboxylated styrene butadiene latex was purchased from Shanghai Gaoqiao BASF Dispersion Co., Ltd., with a brand name of Styrofan SD 8556, a solid content of 50 wt %, a pH of 6.2, a Tg of 2° C., and an average particle size of 150 nm.

[0040] Polyvinyl alcohol was purchased from Shanghai Yanzun Biotechnology Co., Ltd. with a weight-average molecular weight of 43,000.

[0041] PO42.5 silicate cement was purchased from Anhui Conch Cement Co., Ltd.

[0042] The high-efficiency water reducing agent was purchased from BASF, with the brand name Melflux 4930F.

[0043] The fly ash was purchased from Hebei Wenfeng Industrial Group Co., Ltd. The fly ash fineness was 23.6%, the water requirement ratio was 98%, and the 7-day activity index was 95%.

[0044] Example 1

[0045] 1) 100 parts of water glass, 70 parts of carboxylated styrene butadiene latex, 5 parts of polyvinyl alcohol and 825 parts of water were mixed uniformly to prepare a modified solution, and then 100 parts of artificial sand were soaked in the modified solution prepared above at a mass volume ratio of 1:4, and then ultrasonically treated at a power of 300 W and a frequency of 40 kHz for 10 minutes, the water was drained, and the modified artificial sand was dried at 80° C. for standby use;

[0046] 2) Add 100 parts of PO42.5 silicate cement, 20 parts of fly ash, 35 parts of modified artificial sand, 40 parts of coarse aggregate, 1.8 parts of water reducer and 30 parts of water into a mixer and mix until uniform to obtain artificial sand-based PHC pipe pile concrete;

[0047] 3) injecting concrete for artificial sand-based PHC pipe piles into a pipe pile mold, closing the mold, and performing prestressing tensioning treatment on the pipe pile mold after closing the mold, performing centrifugal treatment, steam curing, demoulding, and high-pressure steam curing on the pipe pile mold to obtain an artificial sand-based PHC pipe pile.

[0048] The centrifugal treatment is as follows: a low-speed stage of centrifuging at a speed of 100 r / min for 2 min, a low-medium-speed stage of centrifuging at a speed of 150 r / min for 3 min, a medium-speed stage of centrifuging at a speed of 400 r / min for 3 min, and finally a high-speed stage of centrifuging at a speed of 600 r / min for 5 min.

[0049] Steam curing: stop for 0.5h, heat up to 100℃ at a rate of 25℃ / h, keep constant at 100℃ for 5h, and naturally cool down to room temperature;

[0050] High-pressure steam curing: During the temperature and pressure increase stage, the pressure is increased to 0.88MPa for 2h, the temperature is increased to 180℃, and during the constant temperature and pressure stage, 180℃ and 0.88MPa are maintained at constant temperature and pressure for 5h. During the temperature and pressure reduction stage, natural cooling is adopted, and the reduction rate is 0.3MPa / h.

[0051] Example 2

[0052] The rest is the same as Example 1, except that in step 1), the amount of carboxylated styrene butadiene latex is 50 parts and the amount of water is 845 parts.

[0053] Example 3

[0054] The rest is the same as Example 1, except that in step 1), the amount of carboxylated styrene butadiene latex is 30 parts and the amount of water is 865 parts.

[0055] Example 4

[0056] The rest is the same as Example 1, except that in step 1), the amount of carboxylated styrene butadiene latex is 90 parts and the amount of water is 805 parts.

[0057] Example 5

[0058] The rest is the same as Example 1, except that in step 1), 100 parts of artificial sand are immersed in the previously prepared modifying liquid at a mass volume ratio of 1:2.5.

[0059] Example 6

[0060] The rest is the same as Example 1, except that in step 1), 50 parts of water glass, 70 parts of carboxylated styrene butadiene latex, 10 parts of polyvinyl alcohol, and 870 parts of water are first mixed uniformly to prepare a modified liquid, and then 100 parts of artificial sand are immersed in the modified liquid prepared above at a mass volume ratio of 1:2.5, and ultrasonically treated at a power of 300 W and a frequency of 40 kHz for 10 min, the water is drained, and the modified artificial sand is dried at 80°C for standby use.

[0061] Example 7

[0062] The rest is the same as Example 1, except that the centrifugation in step 3) is: a low-speed stage of centrifuging at a speed of 50 r / min for 3 min, a low-medium speed stage of centrifuging at a speed of 100 r / min for 3 min, a medium-speed stage of centrifuging at a speed of 200 r / min for 5 min, and finally a high-speed stage of centrifuging at a speed of 400 r / min for 10 min.

[0063] Example 8

[0064] The rest is the same as Example 1, except that the amount of modified artificial sand used in step 2) is 25 parts.

[0065] Comparative Example 1

[0066] The rest is the same as Example 1, except that, in step 1), the carboxyl styrene butadiene latex is replaced by an equal mass of styrene butadiene latex Rovene 4813.

[0067] Comparative Example 2

[0068] The rest is the same as Example 1, except that, in step 1), the carboxylated styrene-butadiene latex is replaced by water glass of equal mass.

[0069] Comparative Example 3

[0070] The rest is the same as Example 1, except that polyvinyl alcohol is not added in step 1).

[0071] Comparative Example 4

[0072] The rest is the same as Example 1, except that there is no step 1):

[0073] That is, 1) 100 parts of PO42.5 silicate cement, 20 parts of fly ash, 35 parts of artificial sand, 40 parts of coarse aggregate, 1.8 parts of water reducing agent and 30 parts of water are added to a mixer and mixed until uniform to obtain artificial sand-based PHC pipe pile concrete;

[0074] 2) injecting concrete for artificial sand-based PHC pipe piles into a pipe pile mold, closing the mold, and performing prestressing tensioning treatment on the pipe pile mold after closing the mold, centrifugal treatment, steam curing, demoulding, and high-pressure steam curing on the pipe pile mold to obtain an artificial sand-based PHC pipe pile.

[0075] The centrifugal treatment is as follows: a low-speed stage of centrifuging at a speed of 100 r / min for 2 min, a low-medium-speed stage of centrifuging at a speed of 150 r / min for 3 min, a medium-speed stage of centrifuging at a speed of 400 r / min for 3 min, and finally a high-speed stage of centrifuging at a speed of 600 r / min for 5 min.

[0076] Steam curing: stop for 0.5h, heat up to 100℃ at a rate of 25℃ / h, keep constant at 100℃ for 5h, and naturally cool down to room temperature;

[0077] High-pressure steam curing: During the temperature and pressure increase stage, the pressure is increased to 0.88MPa for 2h, the temperature is increased to 180℃, and during the constant temperature and pressure stage, 180℃ and 0.88MPa are maintained at constant temperature and pressure for 5h. During the temperature and pressure reduction stage, natural cooling is adopted, and the reduction rate is 0.3MPa / h.

[0078] The pipe piles prepared above were subjected to the following performance tests:

[0079] 1. Compressive strength: A 28d strength test was performed with reference to the standard GB / T50081-2019 Test method for physical and mechanical properties of concrete. The specimens were prepared by drilling standard cubic specimens with a side length of 150 mm on the surface of the pipe piles in the above-mentioned embodiment and the comparative example. Three specimens were prepared for each sample, and the average value of the three specimens was taken.

[0080] 2. Freeze-thaw cycle resistance: The test was conducted in accordance with the standard GB / T 50082-2009 Test method for long-term performance and durability of ordinary concrete. Freeze-thaw cycles were performed in tap water and artificial seawater (ASTM D1141-1998 (2013) "Standard Technical Specification for Artificial Seawater"), and the samples were weighed every 25 cycles, and the number of cycles when the mass loss was 5wt% was recorded.

[0081] Table 1 Performance test results

[0082]

[0083]

[0084] It can be seen from Table 1 that the modified artificial sand can significantly improve the frost resistance of pipe pile concrete. The mass loss is within 5wt% after more than 500 freeze-thaw cycles in tap water medium, and the mass loss is controlled within 5wt% after more than 300 freeze-thaw cycles in artificial seawater medium.

[0085] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.

Claims

1. An artificial sand-based PHC pipe pile concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of cement, 20-30 parts of admixture, 25-35 parts of modified artificial sand, 40-55 parts of coarse aggregate, 0.1-1 part of water reducer and 25-40 parts of water. The modified artificial sand is obtained by soaking artificial sand in a modifying liquid and drying the modified liquid. The modifying liquid comprises 5-10wt% of water glass, 5-7wt% of carboxylated styrene butadiene latex and 0.5-1wt% of polyvinyl alcohol. The mass volume ratio of the artificial sand to the modifying liquid is 1:2.5-4g / mL.

2. The artificial sand-based PHC pipe pile concrete according to claim 1, characterized in that: The carboxylated styrene butadiene latex has a solid content of 45-55wt%, a pH of 5.5-7.0, a Tg of 2-10°C, and an average particle size of 100-200nm.

3. The artificial sand-based PHC pipe pile concrete according to claim 1, characterized in that: The modulus of the water glass is 2.0-3.5, and the Baume degree is 30-40; the weight average molecular weight of the polyvinyl alcohol is 30,000-50,000; the fineness modulus of the artificial sand is 2.2-3.0, and the mud content is ≤1.0%.

4. The artificial sand-based PHC pipe pile concrete according to claim 3, characterized in that: The gradation of the artificial sand is 60-70wt% of the artificial sand with a fineness modulus of 2.2-2.5 and 30-40wt% of the artificial sand with a fineness modulus of 2.5-3.

5. The artificial sand-based PHC pipe pile concrete according to claim 1, characterized in that: The admixture is selected from one or a combination of two or more of fly ash, mineral powder, and silica sand powder; preferably fly ash.

6. The method for preparing the artificial sand-based PHC pipe pile concrete according to any one of claims 1 to 5, characterized in that: The steps include: 1) mixing water glass, carboxylated styrene butadiene latex, polyvinyl alcohol and water to obtain a modified liquid, then soaking the artificial sand in the modified liquid, subjecting it to ultrasonic treatment, draining the water, and drying the modified artificial sand for standby use; 2) Add cement, admixture, modified artificial sand, coarse aggregate, water reducing agent and water into a mixer and mix them evenly to obtain concrete for artificial sand-based PHC pipe piles.

7. The artificial sand-based PHC pipe pile concrete according to claim 6, characterized in that: Step 1) The power of the ultrasonic treatment is 300-500W, the frequency is 20-40kHz, the time is 10-20min, and the drying temperature is 60-100°C.

8. Use of the concrete for artificial sand-based PHC pipe piles according to any one of claims 1 to 5 in the preparation of PHC pipe piles.

9. The use of the artificial sand-based PHC pipe pile concrete according to claim 8 in the preparation of PHC pipe piles, characterized in that: The application comprises the following steps: The artificial sand-based PHC pipe pile concrete is injected into the pipe pile mold, the mold is closed, and the pipe pile mold after the mold is closed is subjected to prestressing tensioning treatment, centrifugal treatment, steam curing, demoulding, and high-pressure steam curing to obtain the artificial sand-based PHC pipe pile.

10. The use of the artificial sand-based PHC pipe pile concrete according to claim 9 in preparing PHC pipe piles, characterized in that: The steps of the centrifugation treatment are sequentially: a low-speed stage of centrifuging at a rotation speed of 50-100 r / min for 1-3 min, a low-medium-speed stage of centrifuging at a rotation speed of 100-150 r / min for 1-3 min, a medium-speed stage of centrifuging at a rotation speed of 200-400 r / min for 3-5 min, and finally a high-speed stage of centrifuging at a rotation speed of 400-600 r / min for 5-10 min.

Citation Information

Patent Citations

  • A PHC pipe pile concrete and its preparation method

    CN105541223B